The structure and expression of the murine gene encoding granulocyte-macrophage colony stimulating factor: evidence for utilisation of alternative promoters. - Stanley, E (1985)
Two overlapping genomic clones containing the murine granulocyte-macrophage colony stimulating factor (GM-CSF) gene have been isolated. On the basis of transfection experiments, we have established that a 9-kb BamHI fragment from one of these recombinants encodes biologically active GM-CSF. As deduced from nucleotide sequence analysis, the GM-CSF gene comprises four exons encompassing 2.5 kb of genomic DNA. Primer extension analysis of GM-CSF mRNA identifies a transcriptional initiation site 35 bp upstream of a single translational initiation codon in-frame with the GM-CSF coding sequences and 28 bp downstream of a TATA promoter consensus sequence. Pre-GM-CSF molecules encoded by mRNAs originating from this promoter would include a hydrophobic leader sequence typical for a secreted protein. Intriguingly, sequences present at the 5' end of a GM-CSF cDNA clone previously isolated in our laboratory are not contained within either of the genomic clones and must therefore be transcribed from a promoter located at least 10 kb 5' of the main body of the gene. mRNAs transcribed from this alternative upstream promoter possess an additional initiating codon and potentially encode a pre-GM-CSF polypeptide with an atypical NH2-terminal leader peptide. Comparison of the nucleotide sequence of the GM-CSF gene with that of other haemopoietic growth factor genes has revealed a common decanucleotide (5'-GPuGPuTTPyCAPy-3') within their respective 5'-flanking regions which may be involved in their co-ordinate regulation.